Grocery delivery in the United States : trying to bag profits - Busse, Meghan R. (Meghan Ruth); Springer, Susan (London : Kellogg School of Management, 2022)
Since 1989, U.S. companies have been trying-mostly unsuccessfully-to marry the ease of ordering groceries online with the convenience of home delivery. All have learned that the combination of customer demands, and logistical challenges have made it difficult to be profitable in this space. Unlike retailers of standard items (such as books), sellers of groceries had to exercise judgment when selecting fresh meat, fruits, and vegetables to satisfy consumers' tastes. Once selected, many items needed to be packed in specific ways and required timely delivery to maintain freshness and quality. In addition, the "last mile" of delivery was costly and highly variable between high-density urban customers and those in more dispersed suburban and rural communities.Customers were familiar with in-store prices and resisted paying more, a preference reinforced by Amazon and other online retailers, which had created an expectation that online prices should be the same as-or even lower than-prices in stores. In addition, customers had a strong aversion to delivery charges, even if delivery saved them time. They also much preferred the convenience of narrow time windows for delivery and had a low tolerance for mistakes.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Grocery shopping -- Case studies; Delivery of goods -- Case studies